PENGARUH KEPEMIMPINAN KEPALA SEKOLAH (SCHOOL LEADERSHIP) DAN KEADILAN DISTRIBUTIF TERHADAP KOMITMEN ORGANISASI: Studi Ex Post Facto Terhadap Guru SMP Negeri Di Kabupaten Cirebon - Chintia Aninda; I Made Putrawan; Heru Santosa (Program Studi Manajemen Pendidikan, 2018)
This study aims to: (1) find out the interaction effect of school leadership and distributive justice on the teachers’ organizational commitment (2) to know the difference of the teacher's organizational commitment, between the teachers who judge their bosses to have transformational leadership and the teachers who judge their boss to have transactional leadership, (3) to know the difference in organizational commitment between teachers who receive distributive equity treatment equally unevenly. This study uses quantitative approach with ex post facto method through 2x2 factorial design. The result of hypothesis testing indicates that there is (1) a very significant difference in organizational commitment that assesses school leadership with transformational leadership and transactional leadership, (2) there is a significant difference on the teacher's organizational commitment that assesses the principal with distributive fairness equally unequally, 3) there is a significant interaction influence between school leadership and distributive justice on teacher organizational commitment, (4) in distributive distributive group, teachers' the organizational commitment assesses school principals with transformational leadership higher than transactional leadership, and (5) in unequal distributive justice group, teacher's organizational commitments assesses principals with transformational leadership higher than transactional leadership.